2012
DOI: 10.1111/j.1750-3841.2011.02546.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Sponge Cake Formulation with Inulin as Fat Replacer: Structure, Physicochemical, and Sensory Properties

Abstract: The effects of several fat replacement levels (0%, 35%, 50%, 70%, and 100%) by inulin in sponge cake microstructure and physicochemical properties were studied. Oil substitution for inulin decreased significantly (P < 0.05) batter viscosity, giving heterogeneous bubbles size distributions as it was observed by light microscopy. Using confocal laser scanning microscopy the fat was observed to be located at the bubbles' interface, enabling an optimum crumb cake structure development during baking. Cryo-SEM micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 22 publications
(30 reference statements)
9
89
2
4
Order By: Relevance
“…On the other hand, as the level of oil substitution in cakes with no emulsifier was increased, the bubbles were smaller in number but larger in size. Psimouli and Oreopoulou (2013) and Rodríguez-García et al (2012) also observed a smaller size of bubbles in cakes prepared with shortening and oil, respectively, compared to those with a fat replacer. These authors attributed this effect to the ability of oil to stabilize bubbles by forming a film in the air-matrix interface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, as the level of oil substitution in cakes with no emulsifier was increased, the bubbles were smaller in number but larger in size. Psimouli and Oreopoulou (2013) and Rodríguez-García et al (2012) also observed a smaller size of bubbles in cakes prepared with shortening and oil, respectively, compared to those with a fat replacer. These authors attributed this effect to the ability of oil to stabilize bubbles by forming a film in the air-matrix interface.…”
Section: Resultsmentioning
confidence: 99%
“…With the addition of emulsifier, the hardness was reduced for all the cakes studied. Instead of volume differences, this effect may be due to the fact that the hardness of the cakes was highly sensitive to the air bubble size distribution, as a distribution in small areas resulted in a significantly softer cake (Rodríguez-García et al 2012), this distribution in small areas was also shown in the structure of the crumb. Thus, the way in which the air is retained into the batter during whipping and baking process would affect crumb hardness.…”
Section: Cake Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Confocal laser scanning microscopy (CLSM), light microscopy (LM), and image analysis of batter bubbles were performed according to the methods described by Rodríguez-García et al (2012).…”
Section: Ingredientsmentioning
confidence: 99%
“…A aceitação sensorial pelos bolos neste trabalho foi superior ou igual a outros trabalhos que estudaram a aceitação por bolos adicionados de frutanos (DEVEREUX et. al., 2003;RONDA et al, 2005;RODRÍGUEZ-GARCÍA et al, 2012). Tabela 5.…”
Section: Bolo De Laranjaunclassified